Craniocervical dystonia questionnaire (CDQ-24) : validation and cross-cultural adaptation in Serbian patients - Kisić Tepavčević, Darija (Array, 2009)
Abstract: The purpose of this study was to investigate the validation of the translated and culturally adapted CDQ-24 questionnaire on a group of Serbian patients. The study was comprised of 100 consecutive patients with idiopathic cervical dystonia (CD) and blepharospasm (BSP) who were evaluated at the Institute of Neurology, Clinical Centre of Serbia in Belgrade between March and June 2007. The linguistic validation of CDQ-24 involved 3 steps, according to an internationally accepted methodology. Most of the patients with CD and BSP accepted the CDQ-24 questionnaire. The internal consistency reliability ranged from 0.81 to 0.97. The mean total score of the CDQ-24 was 35.6±23.5. Patients with BSP had better HRQoL scores in the Pain subscale (p=0.025) compared with CD patients. However, patients with CD had better HRQoL sores in the Activities of Daily Living subscale (p=0.028) compared with BSP patients. Statistically significant positive correlations were registered between the Dystonia Movement Scale score and almost all CDQ-24 scales. The Serbian version of CDQ-24 should be recommended for HRQoL evaluation among patients with CD and BSP as an important outcome measure